Some remarks on rare and new Palaearctic species of the genus Zodion Latreille (Diptera: Conopidae) - Stuke, Jens-Hermann (Zootaxa, 2014)
Zodion hispanicum spec. nov. is described from Spain (Murcia, Sierra Espuña) and Zodion hauseri spec. nov. is described from Kazakhstan (Almaty Province, Charyn Valley). A diagnosis is given for Zodion andersoni Kröber, 1936 and Zodion vsevolodi Zimina, 1974. Zodion asiaticum Becker, 1922 is placed as a junior synonym of Zodion cinereum (Fabricius, 1794) (syn. nov.). New faunistic records are presented for Z. andersoni and Z. vsevolodi.